2012
DOI: 10.1021/ic2022769
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Tyr-Cys Cross-link to the Active Site Properties of Galactose Oxidase

Abstract: The catalytically relevant, oxidized state of the active site [Cu(II)-Y·-C] of galactose oxidase (GO) is composed of antiferromagnetically coupled Cu(II) and a post-translationally generated Tyr-Cys radical cofactor [Y·-C]. The thioether bond of the Tyr-Cys cross-link has been shown experimentally to affect the stability, the reduction potential, and the catalytic efficiency of the GO active site. However, the origin of these structural and energetic effects on the GO active site has not yet been investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 76 publications
(155 reference statements)
0
53
0
5
Order By: Relevance
“…Very recently, Rokhsana et al have reported that the Tyr-Cys cross linked sulfur environment is essential for fine-tuning the electronic structure of the GO's active site, 16 and the sulfur environment may be responsible for the selective oxidation of benzylic alcohols over the aliphatic alcohols. We hypothesize that a Cu complex with an N3S coordination environment may mimic the activity of the active site of GO, leading to similar catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, Rokhsana et al have reported that the Tyr-Cys cross linked sulfur environment is essential for fine-tuning the electronic structure of the GO's active site, 16 and the sulfur environment may be responsible for the selective oxidation of benzylic alcohols over the aliphatic alcohols. We hypothesize that a Cu complex with an N3S coordination environment may mimic the activity of the active site of GO, leading to similar catalytic activity.…”
Section: Resultsmentioning
confidence: 99%
“…The electrostatic environment of the protein matrix was approximated using a water-based polarizable continuum model [5658] with a commonly used dielectric constant of ε = 10 for polar protein environment [59]. The effect of the specific value of the dielectric constant in going from 10 to 40 units for the relative energies is expected to be at most 0.2 eV or 20 kJ/mol [60]. …”
Section: Methodsmentioning
confidence: 99%
“…DFT calculations suggest that an orientation of the less sterically demanding -SMe substituent in plane with the phenoxyl ring maximizes S p -orbital overlap with the aromatic π system in [Cu 12 SMe2 ] + , allowing for greater delocalization of the hole onto the sulfur atoms [19]. In a recent sulfur K-edge XAS study of GO ox itself, Rokhsana et al report a sulfur contribution from the Cys-Tyr cross link to the tyrosyl hole of 24 ± 3 % [50]. This value is in good agreement with previous electron paramagnetic resonance (EPR) studies of apo-GO ox that predicted a value of 20 ± 3 % [51].…”
Section: Characterization Of Oxidized Salen Complexesmentioning
confidence: 99%